Human growth hormone responses to repeated bouts of sprint exercise with different recovery periods between bouts - Stokes, K.; Nevill, M.; Frystyk, J.; Lakomy, H. K. A.; Hall, G. (Journal of Applied Physiology, 2005)
This study examined the growth hormone (GH) response to repeated bouts of sprint cycling. Eight healthy men completed three trials consisting of two 30-s sprints on a cycle ergometer separated by either 60 min (Trial A) or 240 min (Trial B) of recovery and a single 30-s sprint carried out the day after Trial B (Trial C). Trials A and B were separated by at least 7 days. Blood samples were obtained at rest and during recovery from each sprint. In Trial A, GH was elevated immediately before sprint 2, and there was no further increase in GH following the second sprint [area under the curve: 460 (SD 348) vs. 226 min·µg-1·l-1 (SD 182), P = 0.05]. Free insulin-like growth factor I tended to be lower immediately before sprint 2 than sprint 1 (P = 0.06). Serum free fatty acids were not different immediately before each of the sprints. In Trial B, there was a trend for a smaller GH response to the second sprint [GH area under the curve: 512 (SD 396) vs. 242 min·µg-1·l-1 (SD 190), P = 0.09]. Free insulin-like growth factor I tended to be lower (P = 0.06), and serum free fatty acids were higher (P = 0.01) immediately before sprint 2 than sprint 1. There was no difference in the GH response to sprinting on consecutive days (Trials B and C). In conclusion, repeated bouts of sprint cycling on the same day result in an attenuation or even ablation of the exercise-induced increase in GH, depending on the recovery interval between sprints.